2014
DOI: 10.1051/0004-6361/201423726
|View full text |Cite
|
Sign up to set email alerts
|

K-shell energy levels and radiative rates for transitions in Si ix

Abstract: Context. Accurate atomic data are needed to analyze the Si ix K-shell features in astrophysical X-ray spectra. Relative large discrepancies in the existing atomic data have impeded this progress.Aims. We present the accurate Si ix K-shell transition data, including K-shell energy levels, wavelengths, radiative rates, and oscillator strengths. Methods. The flexible atomic code (FAC), which is a fully relativistic atomic code with configuration interaction (CI) included, was employed to calculate these data. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Many of these atomic parameters have been measured in the laboratory for L-shell Si ions (see Faenov et al (1994); Kramida & Träbert (1995); Vilkas et al (2005); Hell et al (2016) and references in there). Multiple systematic (Behar & Netzer 2002; Gu 2005; Liang et al 2007; Palmeri et al 2008; Karim 2011; Wang et al 2011; Hell et al 2016) and targeted (Orloski & Trigueiros 2001; Wei et al 2010; Tayal 2012; Sossah & Tayal 2015; Wei et al 2014) calculations have complemented the measurements. Atomic data has also been provided by calculations of the isoelectronic sequence of various L-shell ions (Safronova & Shlyaptseva 1996; Jönsson et al 2011; Rynkunb et al 2012; Jönsson et al 2013, 2014; Rynkunb et al 2014; Nazé et al 2014; Wang et al 2014, 2015, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these atomic parameters have been measured in the laboratory for L-shell Si ions (see Faenov et al (1994); Kramida & Träbert (1995); Vilkas et al (2005); Hell et al (2016) and references in there). Multiple systematic (Behar & Netzer 2002; Gu 2005; Liang et al 2007; Palmeri et al 2008; Karim 2011; Wang et al 2011; Hell et al 2016) and targeted (Orloski & Trigueiros 2001; Wei et al 2010; Tayal 2012; Sossah & Tayal 2015; Wei et al 2014) calculations have complemented the measurements. Atomic data has also been provided by calculations of the isoelectronic sequence of various L-shell ions (Safronova & Shlyaptseva 1996; Jönsson et al 2011; Rynkunb et al 2012; Jönsson et al 2013, 2014; Rynkunb et al 2014; Nazé et al 2014; Wang et al 2014, 2015, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these calculations focused on valence level energies, and only a limited number of them deals with K-vacancy level energies (Safronova & Shlyaptseva 1996; Behar & Netzer 2002; Palmeri et al 2008; Wei et al 2010; Karim 2011; Wang et al 2011; Wei et al 2014; Hell et al 2016). Moreover, valence level energies have been studied to a high level of accuracy with large-scale Relativistic Configuration Interaction (RCI) (Jönsson et al 2011; Rynkunb et al 2012; Jönsson et al 2013, 2014; Rynkunb et al 2014; Nazé et al 2014) and combining RCI with Many-Body Perturbation Theory approaches (Vilkas et al 2005; Wang et al 2014, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the effects of different atomic data on the calculated absorption spectra, we adopted the same configurations as those in the work of Palmeri et al (2008), who calculated the K-shell atomic data. For Be-like and C-like ions, the accuracy of the K-shell data was described in our previous work (Wei et al 2010(Wei et al , 2014). The energy levels are generally accurate to a few eV (less than 4 eV), the wavelengths to within 15 mÅ, and the radiation to around 20% for most transitions.…”
Section: Modelmentioning
confidence: 99%
“…Fortunately, since the launch of high resolution X-ray satellites (Chandra and XMM), K-shell atomic data have been extensively calculated (Palmeri et al 2002(Palmeri et al , 2008(Palmeri et al , 2011(Palmeri et al , 2012Behar & Netzer 2002;Bautista et al 2003Bautista et al , 2004Mendoza et al 2004;Witthoeft et al 2009;Wei et al 2010Wei et al , 2014. Among these works, Palmeri et al (2008) reported firstly the K-shell data for M-shell ions of Ne, Mg, Si, S, Ar, and Ca with the codes HFR (Cowan 1981) and AUTOSTRUCTURE (Badnell 1986(Badnell , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical calculations [4,[9][10][11] have been performed to derive the wavelengths and transition rates of K-shell lines using kinds of atom structure codes. These include using HFR [12] and AUTOSTRUCTURE [13,14] to calculate the wavelength and A-values of K-shell lines for some medium-Z elements.…”
Section: Introductionmentioning
confidence: 99%